Effects of extracts of two Ulva spp. seaweeds on tomato germination and seedling growth (Research, Society and Development, 2020)
Brown seaweed extracts are commercially used as agricultural biostimulants, and the green macroalgae Ulva spp. has shown promise for that purpose. We evaluated the ideal dosage of U. lactuca ulvan and flour on seed germination invigoration and the effects of U. flexuosa and U. lactuca extracts on tomato seedling growth (Solanun lycopersicum). The germination recovery of aged seeds after the application of U. lactuca was evaluated by seed germination rates and seedling emergence. Greenhouse cultivated seedlings were irrigated with 0.2 and 0.4 g×L-1 of the flour, or an ulvan solution of Ulva spp. Seedling growth parameters (height, stem diameter, height/stem diameter ratio, biomass, and number of leaves) were compared with the control (seedlings irrigated with distilled water). All dosages of U. lactuca ulvan and flour were found to increase the germination rates of aged seeds as compared to controls. No significant difference in seedling emergence rates were seen. After treatment with Ulva spp. extracts no significant differences in seedling growth were detected. We concluded that low doses of the U. lactuca extract will increase the germination rates of S. lycopersicum seeds and, while different dosages of the extracts of two Ulva’s species did not stimulate tomato seedling growth, they were also not lethal.